Pengaruh Lama Fermentasi Ekoenzim Asal Campuran Feses Sapi Potong Dan Jerami Padi Terhadap Total Bakteri, Kadar Alkohol dan pH - Arwadani, Iswari; Marlina, Eulis Tanti; Hidayati, Yuli Astuti (Jurnal Teknologi Hasil Peternakan, 2024)
The increase in waste volume from the livestock and agriculture sectors requires effective management strategies, including the utilization of eco-enzyme production. Eco-enzymes are versatile liquids made from organic waste, sugar, and water. Generally, eco-enzymes are produced from fruit and vegetable waste; however, evolving information indicates that eco-enzymes can be derived from various types of waste, including livestock waste. The objective of this research is to evaluate the impact of fermentation duration and determine the optimal fermentation period for eco-enzymes derived from a mixture of beef cattle feces and rice straw, specifically focusing on total bacteria, alcohol content, and pH. The research method used was experimental, employing a Completely Randomized Design (CRD), with One-way Anova and Tukey test as the statistical analyses. Four fermentation duration treatments were examined: P1 (7 days), P2 (14 days), P3 (21 days), and P4 (28 days), each replicated five times. The results showed that fermentation duration significantly influenced the pH value, but had no effect on total bacteria and alcohol content. A 28-day fermentation period was identified as the optimal duration for producing eco-enzymes with the highest quality, with the lowest pH reaching 3.45